Perspective of quranic verses of business ethics on justice and honesty in trade - Khoirudin Khoirudin; Adnan Azzaki (Nur Science Institute, 2024)
This study examines the concept of business ethics from an Islamic perspective, highlighting two key principles: justice (adl) and honesty (siddiq), which are pertinent in addressing modern trade challenges. The digital era presents various issues, such as information manipulation and transparency concerns, often disadvantaging consumers. Employing a qualitative descriptive approach, the research utilizes thematic interpretation of Quranic verses, including QS. Al-Baqarah [2]: 282 and QS. Al-Mutaffifin [83]: 1-3, to explore how these principles can be applied in contemporary business ecosystems. The findings reveal that implementing justice and honesty strengthens consumer trust, enhances customer loyalty, and supports business objectives. The study proposes recommendations, including the integration of Islamic ethical values into digital business operations, strengthening of government regulations, improvement of Islamic financial literacy, and public education initiatives.